Respons Radioterapi Karsinoma Serviks Stadium Lanjut Jenis Sel Skuamosa dan Adenokarsinoma di RSUD Ulin, Banjarmasin, Indonesia: Hasil Penelitian - Sindunata, Natasha Bharat; Pratiwi, Eka Indah; Lubis, Arlavinda Asmara (PT Kalbe Farma Tbk., 2025)
Introduction: Cervical carcinoma (cancer) is a malignancy in the cervix and is one of the most common cancers in women. Data released by GLOBOCAN in 2022 showed that cervical cancer ranks eighth globally. The main treatment for advanced cervical cancer is radiotherapy. The aim of this study is to compare the radiotherapy response in squamous cell carcinoma cervical cancer with the response in adenocarcinoma cervical cancer at Ulin Regional Hospital, Banjarmasin, Indonesia. Methods: This cross-sectional research used an analytical observational design. Total sample during the research period from January 2021 to December 2022. Results: Total of 128 cervical cancer patients consisting of 91 squamous cell carcinomas and 37 adenocarcinomas. Chi-square analysis found a significant association between histopathology and response to therapy; squamous cell carcinoma histopathology was more radiosensitive than adenocarcinoma. Conclusion: Histopathological type is the only characteristic significantly associated with radiation response, whereas age, stage, and tumor size are not significantly associated with radiation response.